Microbial Life of Cave Systems - Ariño, Xavier; Benavente, David; Bräuer, Suzanna L.; Carmichael, Sarah; Cañaveras, Juan Carlos; Chen, Yin; Cronan, Andrew; Cuezva, Soledad; Elbourne, Liam; Fernandez-Cortez, Angel; Garcia-Anton, Elena; Gillings, Michael; et al. (Life in Extreme Environments ;, 2015)
The earth's subsurface contains abundant and active microbial biomass, living in water, occupying pore space, and colonizing mineral and rock surfaces. Caves are one type of subsurface habitat, being natural, solutionally- or collapse-enlarged openings in rock. Within the past 30 years, there has been an increase in the number of microbiology studies from cave environments to understand cave ecology, cave geology, and even the origins of life. By emphasizing the microbial life of caves, and the ecological processes and geological consequences attributed to microbes, this book provides the first authoritative and comprehensive account of the microbial life of caves for students, professionals, and general readers.